Apoptotic and proliferative processes in the small intestine of rats with type 2 diabetes mellitus after metformin and propionic acid treatment - Natrus, Larysa; Lisakovska, Olha; Smirnov, Anton; Osadchuk, Yuliia; Klys, Yuliia (Frontiers in Pharmacology, 2024)
Background: Propionic acid (PA) is an intermediate product of metabolism of intestinal bacteria and may protect the intestinal barrier from disruption. The aim of the study was to investigate the apoptotic and proliferative processes in the small intestine (SI) of rats with type 2 diabetes mellitus (T2DM) on the background of metformin monotherapy and its combination with PA.Methods: Male Wistar rats were divided: 1) control; 2) T2DM (3-month high-fat diet followed by streptozotocin injection of 25 mg/kg of body weight); 3) T2DM+metformin (60 mg/kg, 14 days, orally); 4) T2DM+PA (60 mg/kg, 14 days, orally); 5) T2DM+PA+metformin. Western blotting, RT-PCR, and transmission electron microscopy were performed.We observed profound changes in the SI of diabetic rats suggesting the disturbed intestinal homeostasis: impaired mitochondrial ultrastructure, increased cristae volume, and decreased content of proliferative marker Ki67 with almost unchanged proapoptotic caspase-3 and its p17 subunit levels. Metformin and PA monotherapies also led to an increased cristae volume, however, after their combination, a tendency to normalization of ultrastructure of mitochondria was observed. While there was a significant inhibition of proliferation in T2DM and, in greater extent, after metformin and PA monotherapies, differential influence on apoptosis in the SI was observed. While metformin inhibited apoptosis via Bax declining, PA mainly acted via caspase-3-dependent mechanism elevating its active p17 subunit. Conclusion: PA supplementation for the improvement of diabetes-induced gastrointestinal complications concurrently with metformin may be consider as a perspective supportive therapy. Data related to PA action on SI may be valuable during the development of new treatment strategies for diabetes-induced intestinal disturbances raised after metformin treatment.